Research methods for social work, 6th edition - Rubin, Allen; Babbie, Earl R. ([S.l.] : Thomson Brooks/Cole, 2008)
This best-selling text that has empowered more than 100,000 students just like you! Considered the best social work research methods resource, RESEARCH METHODS FOR SOCIAL WORK balances essential content with enlightening examples, consistently revealing the important connections between real research and true-to-life social work practice.
Keywords: Social service--Research--Methodology